CITRA PEREMPUAN DALAM CERPEN KAMBOJA DI ATAS NISAN KARYA HERMAN RN: KAJIAN KRITIK SASTRA FEMINIS (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
This study aimed to describe texts that discussing about the image of women in the short story Kamboja di Atas Nisan karya Herman R.N by using a feminist literary criticism approach. The data of study are texts of the short story Kamboja di Atas Nisan karya Herman R.N. The data are collected through reading and noting. They are analysed by using the qualitative descriptive technique with reference to feminist literary criticism. The results of research shows that the image of women in the short story Kamboja di Atas Nisan are: 1) women's rights in education; 2) the struggle of a mother; 3) the struggle of Kamboja; and 4) the task of a woman in the view of men. In addition, the results of the study indicates that the image of women found in the short story Kamboja di Atas Nisan was in line with the view of feminist literary criticism aimed to obtain a just and equal position and role between women and men in society.